2010
DOI: 10.3168/jds.2009-2788
|View full text |Cite
|
Sign up to set email alerts
|

Use of milk fatty acids composition to discriminate area of origin of bulk milk

Abstract: The fatty acid composition of cow milk, collected in a survey from 19 dairy farms in the border area between Italy and Slovenia, was investigated for 2 consecutive years (2005 and 2006) to assess the possibility of discriminating the area of the origin of the milk. Farms were selected based on diet, animal breed, and farm management to represent the local variability of the systems. In Slovenian farms, grass silage and hay prevailed over corn silage and concentrate feeds, whereas in Italian farms, hay and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
3
21
1
1
Order By: Relevance
“…Several nutritionist Associations recommend the intake of higher levels of cis-MUFA in milk despite of SFA levels (Kris-Etherton, 1999). The content in cis-MUFA found in the present research is quite similar to data reported in the recent literature (Mansson, 2008;Soyeurt et al, 2008;Heck et al, 2009;Gaspardo et al, 2010), with some exceptions: in particular, the C14:1cis9 and C16:1cis9 levels were higher, whereas C18:1cis9 showed slight lesser levels than those reported by Mansson (2008), Soyeurt et al (2008) and Gaspardo et al (2010). Also the desaturase indexes overlap with those reported by other authors, with slightly reduced Δ14 levels (Schennink et al, 2008;Heck et al, 2009;Garnsworthy et al, 2010).…”
Section: Fat Globules Size and Fatty Acids Contentsupporting
confidence: 76%
“…Several nutritionist Associations recommend the intake of higher levels of cis-MUFA in milk despite of SFA levels (Kris-Etherton, 1999). The content in cis-MUFA found in the present research is quite similar to data reported in the recent literature (Mansson, 2008;Soyeurt et al, 2008;Heck et al, 2009;Gaspardo et al, 2010), with some exceptions: in particular, the C14:1cis9 and C16:1cis9 levels were higher, whereas C18:1cis9 showed slight lesser levels than those reported by Mansson (2008), Soyeurt et al (2008) and Gaspardo et al (2010). Also the desaturase indexes overlap with those reported by other authors, with slightly reduced Δ14 levels (Schennink et al, 2008;Heck et al, 2009;Garnsworthy et al, 2010).…”
Section: Fat Globules Size and Fatty Acids Contentsupporting
confidence: 76%
“…Although previous studies reported similar results that, using milk FA profile, the difference between grazing and confinement feeding was correctly classified (Gaspardo et al 2010;Capuano et al 2014), there are very few studies investigating the detailed feeding management in each farm. Although previous studies reported similar results that, using milk FA profile, the difference between grazing and confinement feeding was correctly classified (Gaspardo et al 2010;Capuano et al 2014), there are very few studies investigating the detailed feeding management in each farm.…”
Section: Actualmentioning
confidence: 82%
“…The present study indicated that, using a combination of 16 milk FAs, 90% of the milk samples in each grazing and confinement season were correctly classified into each season. Although previous studies reported similar results that, using milk FA profile, the difference between grazing and confinement feeding was correctly classified (Gaspardo et al 2010;Capuano et al 2014), there are very few studies investigating the detailed feeding management in each farm. The results of the present study indicated that 10% of the milk samples were not classified correctly or were borderline in each season.…”
Section: Actualmentioning
confidence: 85%
See 1 more Smart Citation
“…Actually, these methods are useful tool in the quality control of dairy products (Gaspardo, Lavren ci c, Levart, Del Zotto, & Stefanon, 2010;Hammami et al, 2010;Karoui, Mounem, Rouissi, & Blecker, 2011;Lerma-García, Gori, Cerretani, Simó-Alfonso, & Caboni, 2010;Ochi et al, 2010;Sacco et al, 2009;Sola-Larrañaga & Navarro-Blasco, 2009;Souza et al, 2011).…”
Section: Introductionmentioning
confidence: 99%